A porohyperelastic finite element model of the eye: the influence of stiffness and permeability on intraocular pressure and optic nerve head biomechanics. Issue 6 (25th April 2016) - Ayyalasomayajula, Avinash; Park, Robert I.; Simon, Bruce R.; Vande Geest, Jonathan P.
Abstract : Progressively deteriorating visual field is a characteristic feature of primary open-angle glaucoma (POAG), and the biomechanics of optic nerve head (ONH) is believed to be important in its onset. We used porohyperelasticity to model the complex porous behavior of ocular tissues to better understand the effect variations in ocular material properties can have on ONH biomechanics. An axisymmetric model of the human eye was constructed to parametrically study how changes in the permeabilities of retina–Bruch's–choroid complex, sclera, uveoscleral pathway, and trabecular meshwork as well as how changes in the stiffness of the lamina cribrosa (LC) and sclera affect IOP, LC strains, and translaminar interstitial pressure gradients (TLIPG). Decreasing from 5 × 10 − 12 to 5 × 10 − 13 m/s increased IOP and LC strains by 17%, and TLIPG by 21%. LC strains increased by 13% and 9% when the scleral and LC moduli were decreased by 48% and 50%, respectively. In addition to the trabecular meshwork and uveoscleral pathway, the retina–Bruch's–choroid complex had an important effect on IOP, LC strains, and TLIPG. Changes in and scleral modulus resulted in nonlinear changes in the IOP, and LC strains especially at the lowest and . This study demonstrates that porohyperelastic modeling provides a novel method for computationally studying the biomechanical environment of the ONH. Porohyperelastic simulations of ocular tissues may help provide further insight into the complex biomechanical environment of posterior ocular tissues in POAG.